FEATURES OF FORMATION OF THE MECHANISM OF MANAGEMENT OF SOCIAL INTERACTION OF TRADING ENTERPRISES WITH STAKEHOLDERS - LIASHUK, KATERYNA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article is devoted to the development of an algorithmic method of identification and ranking of key stakeholders for commercial enterprises. The study showed that the main purpose of forming a mechanism for managing the interaction of trade enterprises with stakeholders is to achieve strategic goals of sustainable development and ensure positive results for the company itself and for all stakeholders. Following the principles of sustainable development puts forward the need for companies to move to holistic management. The goals of stakeholder interaction management are social excellence, development of competencies, ensuring sustainable development-oriented cooperation. To achieve organizational efficiency of the management mechanism, the stages of its implementation are proposed, which form a closed management cycle capable of self-improvement. The first stage involves determining the main and additional objectives of the interaction, taking into account the strategic objectives of sustainable development of the trading company. In the second stage, it is proposed to select key stakeholders. The proposed identification algorithm allows for consistent criteria selection, coordination of significant in terms of importance and timing for both parties social projects, to form action plans for their implementation. According to the proposed methodology, a stakeholder can be considered key at a certain point in time, if its economic interests and social expectations coincide with the priorities of sustainable development of the enterprise itself. The third stage of implementation of the management mechanism is proposed to focus on defining the strategy, tools and channels of communication with stakeholders. The fourth stage is the planning of interaction projects, the fifth is the implementation of measures, the sixth is the internal assessment of the effectiveness of management with elements of social audit, the results of which provide for the seventh stage - corrective measures followed by a return to the first stage. Management with elements of risk management is proposed to be introduced in four key areas: compliance with current legislation, organizational improvement, management of current business risks and expanding the technological framework for cooperation with stakeholders. The introduction of these recommendations in the practice of commercial enterprises will increase their reputational status, provide greater transparency of economic activities and social initiatives, which will positively affect sustainable development and ultimately lead to increased capitalization of the enterprise. As a result of the implementation of the proposed measures, the trading company, its stakeholders and society will receive additional positive social results. Further research should be directed towards the organization of effective interaction of trade enterprises with consumers to increase the level of perception of social responsibility projects.
Keywords: sustainable development; social responsibility; social projects; strategic goals; stakeholders; management